Is BAM 50? - Druzhinina, Inna (project baikal, 2025)
Taking into account the results of the analyses of chronology of the BAM track laying, five stages of the main line construction have been defined and graphically represented on the sketch map. Justification was based on the historical context. On the basis of archival materials of museums, open sources and personal recollections of specialists, the author highlights the implemented and unimplemented projects in the towns and villages of BAM in the Irkutsk Oblast. The belonging of some towns and settlements of the first stages of construction to BAM is not always obvious and does not find a worthy place in the chain of events. The article outlines objective reasons and circumstances that influenced it. It also defines urban specificity of settlements of the Soviet period of the western section of BAM.